Looking at lovemaking : constructions of sexuality in Roman art, 100 B.C.-A.D. 250 - Clarke, John R., 1945- (University of California Press, 1998)
What did sex mean to the ancient Romans? In this lavishly illustrated study, John R. Clarke investigates a rich assortment of Roman erotic art to answer this question-and along the way, he reveals a society quite different from our own. Clarke reevaluates our understanding of Roman art and society in a study informed by recent gender and cultural studies, and focusing for the first time on attitudes toward the erotic among both the Roman non-elite and women. This splendid volume is the first study of erotic art and sexuality to set these works-many newly discovered and previously unpublished-i.